Analisis Manajemen Sarana Prasarana Di SMA Negeri 2 Jonggol - Sipa, Susan Ayu; Rahmi, Rahmi; Aziz, Hanan Zein Abdul; Jaelani, Ahmad; Royhan, Muhammad; Muhtadin, Muhtadin; Hidayatullah, Muhammad Taufik (Annusfy : Journal of Multidisciplinary Research, 2026)
This study aims to analyze management  of  facilities at 2 Jonggol Public High School.. The availability and proper management of  facilities and infastructures can create an effective, efficient, and conducive learning environment. The research method used  was an approach through PLP (School Field Introduction) activities and an analysis of fascilities and infastructure management at 2 Jonggol Public High School, which includes planning, procurement, utilization,  maintenance, and suvervision. Data were collected through observation, interviews, and documentation. The research  subjects consist of the principal, vice principal, the division of facilities and infastructures, and educational staff. The result  show that  the management of facilities and infastructure  at 2 Jonggol Public High School has been implemented quite well through the stages of planning, procurement, utilization, maintenance, and supervision. The planning process is carried out by indentifying school needs based on priorities and budget availibility. Procurement of facilities and infastructurse is conducted gradually in line with school development. The utilization of available facilities show improvement in supporting the learning process, although there are still obstacles in the aspects of maintenance and equal distribution of facility use